Determinants of Underpricing in Islamic and Non-Islamic Shares on IPO - Setya, Vabila Ananta; Supriani, Indri; Fianto, Bayu Arie (IAIN Surakarta, 2020)
This study aims at investigating the factors affecting the share’s underpricing in service companies of the Initial Public Offering (IPO) on the Indonesia Stock Exchange (IDX) covering the period from 2011 to 2017. Compared to the precedent studies, this study provides an empirical comparison between Islamic and non-Islamic shares on 22 underpricing stock samples from 44 IPOs in Islamic service shares and 21 underpricing samples from 32 IPOs in non-Islamic service shares. This study adopts a multiple linear regression analysis and an independent sample t-test method. It is revealed that the underwriter's reputation and auditor's reputation have a significant effect on the underpricing of IPO on IDX, both in Islamic and non-Islamic service companies. The result of independent samples t-test indicates that Islamic service shares companies have better financial performance compared to non-Islamic service shares companies. Predicated upon the results, this study implicatively insinuates that companies based on Shariah compliance could anticipate the underpricing level more expeditiously since the Shariah principles are in line with the decreasing level of underpricing.